2005
DOI: 10.1002/pbc.20436
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Wilms tumor according to SIOP 9 protocol in Casablanca, Morocco

Abstract: These results are encouraging for a developing country but special efforts should be done to reduce the rate of abandonment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
37
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 20 publications
4
37
1
Order By: Relevance
“…Clinically more relevant is the resectability of tumours after preoperative chemotherapy; 14% of patients (8/58) had unresectable disease after preoperative chemotherapy and in six patients this was because of metastatic disease. These findings reflect late presentations, as does the fact that only 22% of tumours of the localized tumours were stage I at surgery in our study, compared to 64% in SIOP 9 and 53% in Casablanca [3,12]. There was also a high (20%) rate of tumour rupture at surgery, compared to 1-3% in the SIOP 9 study in localized tumours and to 21% (14/67) in a selected group of patients with tumours exceeding 1,000 g at surgery in Durban, South Africa [3,11].…”
Section: Discussionsupporting
confidence: 57%
“…Clinically more relevant is the resectability of tumours after preoperative chemotherapy; 14% of patients (8/58) had unresectable disease after preoperative chemotherapy and in six patients this was because of metastatic disease. These findings reflect late presentations, as does the fact that only 22% of tumours of the localized tumours were stage I at surgery in our study, compared to 64% in SIOP 9 and 53% in Casablanca [3,12]. There was also a high (20%) rate of tumour rupture at surgery, compared to 1-3% in the SIOP 9 study in localized tumours and to 21% (14/67) in a selected group of patients with tumours exceeding 1,000 g at surgery in Durban, South Africa [3,11].…”
Section: Discussionsupporting
confidence: 57%
“…The LTFU rate was 13.2%, which is less than the 20% reported in a Moroccan cohort. 22 This is perhaps a result of subsidized chemotherapy and social supports at BCCOE 5,6 ; however, we currently do not have sufficient data to evaluate contributing factors. Relapse rates may also be probed in the future with additional data.…”
Section: Discussionmentioning
confidence: 99%
“…The units with an established multidisciplinary approach before the beginning of this study treated the largest number of patients according to the protocol [10,11]. Some units were unable to contribute significantly to this study either because the surgeons were not convinced of the value of preoperative chemotherapy or because of a paucity of resources at all levels.…”
Section: Discussionmentioning
confidence: 99%
“…The SIOP studies demonstrated the value of preoperative chemotherapy [3] to limit the risk of tumor rupture during surgery, to increase the percentage of stage I tumors requiring less aggressive treatments and to limit complications associated with surgery [9]. In Africa, the results of such treatment management are fragmentary [10][11][12][13] or are unknown.…”
Section: Introductionmentioning
confidence: 99%